Evidence‐based Practice Intentions and Long‐term Behaviours of Physiotherapy Graduates Following an Intensive Education Programme. (24th February 2016) - Perraton, L.; Machotka, Z.; Gibbs, C.; Mahar, C.; Kennedy, K.; Grimmer, K.
Abstract: Background: Assisting physiotherapists to implement research evidence into clinical practice is essential to ensure the quality of practice and encourage lifelong learning and professional progression. However, many physiotherapists report barriers to implementing research, and there is little evidence regarding the sustainability of intended evidence‐based practice (EBP) behaviours following EBP education programmes. This paper reports on intended and actual long‐term EBP behaviours of physiotherapy students who completed an intensive EBP training programme embedded within a post‐graduate coursework programme. Methods: An intensive 3‐week course in quantitative health research methods and EBP was delivered annually from 2007 to 2014 as part of the programme to national and international students. Following the course, students were asked about their intention of using evidence to inform their future clinical practice. An online survey was used to evaluate EBP behaviours of graduates. Results: Of a possible total of 202 students, contact details for 193 students were sourced, and 65 students responded to the survey (34% response rate). At course completion, 174 students (86%) indicated that they intended to use research to guide their clinical decisions at least once a week. At follow‐up, most graduates reported frequently using research to inform their clinical practice; indicated by a mean score of 6.5 (±1.9) from a possible range of 0 (not at all) to 10 (all the time). On average, students reported spending 2.2 (±2.2) hours accessing and reading research evidence per week. The most common barriers to implementing evidence were lack of time, limited access to evidence sources and a perceived lack of generalizability of research findings to specific patient groups. Conclusion: Graduates of an intensive EBP training programme embedded within an existing post‐graduate physiotherapy programme regularly implemented EBP in clinical practice. Barriers to evidence implementation were time, access to research and perceived lack of generalizability of research findings. Copyright © 2016 John Wiley & Sons, Ltd.